Strand 2: New Media in the University of Helsinki: Information and Communication Strategy and its Implementation - Hilkka, Ailio; Petrus, Kaartinen; Jyrki, Kanerva; Teo, Kirkinen; Jari, Salminen; Marja, Venna (Proceedings of the International Conference on Networked Learning, 1998)
The University of Helsinki has developed a strategy for using information and communication technologies in university education. This strategy is summarized and some concrete technical applications are briefly presented, including the use of virtual seminars on the WWW, the production of a multimedia CD-ROM on Finnish history and the integration of remote classrooms through video conferencing.